Transforming Identities in Contemporary Europe Critical Essays on Knowledge, Inequality and Belonging - Engebretsen, Elisabeth Lund; Liinason, Mia (Taylor & Francis, 2023)
Interdisciplinary in perspective, this book explores contemporary struggles around 'identity politics' in Europe, offering a unique glimpse into contemporary tensions and paradoxes surrounding identities, belonging, exclusions and their deep-seated gendered, colonial and racist legacies. With a particular focus on the Nordic region, it provides insights into the ways in which people who find themselves in minoritized positions struggle against multiple injustices. Through a series of case studies documenting counter-struggles against racist, colonialist, sexist forms of discrimination and exclusion, Transforming Identities in Contemporary Europe asks how the paradigm and politics of the welfare state operates to discriminate against the most marginalized, by instating a naturalized hierarchy of human-ness. As such it will appeal to scholars across the social sciences and humanities with interests in race, gender, colonialism and postcolonialism, citizenship and belonging.